ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT. GARUDA INDONESIA (PERSERO) TBK (PERIODE 2010 – 2014) - Gregorius Kirene; Silvia Indrarini; MAF. Suprapti (Universitas Katolik Widya Karya Malang, 2020)
This research is about analysis of financial ratios in PTGaruda Indonesia (Persero) Tbk in 2010 to 2014. This studyaims to determine the financial ratio analysis that can beused to assess the financial performance of PT GarudaIndonesia in 2010-2014. Types of financial ratios that wereused are the liquidity ratios, activity ratios, solvability ratios,profitability ratios, and the market ratio. The data that areused is in the form of an annual financial statement data ofPT Garuda Indonesia (Persero) Tbk from 2010 to 2014. Thisstudy used quantitative descriptive analysis techniques.The analysis showed that, the best value of any rate in theperiod of 2010-2014 is a current ratio in 2011 that is 1.1563,the quick ratio is 1.0335 in 2011, the cash ratio is 0.5666 in2011. The best value of total assets turnover was in 2011 at1.5083, fixed assets turnover at 5.3839 in 2011, the averageage of receivables is at 11.8038 in 2014 and accountsreceivable turnover is at 0.0276 in 2013. The best solvabilityratio is debt ratio in 2012 that is 0.5572 and a total debt toequity ratio of 0.8482 in the year 2011. The best profitabilityratio value are gross profit margin in 2012 amounted to0.0436, the net profit margin at 0,0319 in 2012, basicearning power at 0.0602 in 2012, return on investment at0.0449 in 2011 and return on equity is at 0.0962 in 2012.The best value of market ratio from 2010-2014 is earningsper share which is at 48.9566 in 2012, the ratio of profitprice at 101.0734 in 2013 and the ratio of market value by1.34 per book in 2012.